Writing and the Productive Agricultural Scientist - LaRae M. Donnellan; Susan M. Ross (Journal of Applied Communications, 1990)
At a Northeastern land-grant university, 87% of Experiment Station scientists thought that writing was part of their responsibility as scientists.